Effect of Using Capsules with Waste Mineral Oil on Self-Healing of Long-Term Aged Hot-Mix Asphalt - Bakir, Esma; Yalcin, Erkut; Yilmaz, Mehmet; Kok, Baha Vural; Hernandez, Alvaro Garcia (Asce-Amer Soc Civil Engineers, 2023)
Capsules containing waste mineral oil can delay the maintenance of asphalt mixtures by preventing the spread of cracks. As a result of the encounter between the crack and capsule, the capsule breaks and releases the restorative material inside the crack area, resulting in healing. This experimental research demonstrated the rate at which oil is released from the capsules when the asphalt is subjected to cyclic loading and four different cures (24 h at 25 degrees C, 48 h at 25 degrees C, 24 h at 40 degrees C, and 48 h at 40 degrees C), and the capacity of asphalt to improve its inherent self-healing capacities in terms of cracks. In the study, the effects of capsule amount, curing time, and temperature on the mixtures were examined. Three-point bending fatigue tests and Fourier transform infrared spectroscopy (FTIR) tests were used in the study. It was determined that the capsules were broken and oil was released when cracks started to form in the hot-mix asphalt. The experiments showed that increasing the amount of capsules increased the oil release and the recovery rate, but decreased the mechanical performance by reducing the fatigue life. It was also found that the increase in curing time and temperature increased the recovery rate. Finally, the effects of capsule content and load characteristics on the healing index were defined by response surface method (RSM).
Keywords: Self-healing; Asphalt mixture; Cure; Capsules; Cracking; Response surface method (RSM)